Postpartum Empowerment through Postnatal Care Education for Enhanced Maternal Health in Wetland Areas - Dewi, Yulia Irvani; Erika, Erika; Lestari, Widia; Misrawati, Misrawati; Utami, Sri; Tampubolon, Masrina Munawarah; Novayelinda, Riri; Indriati, Ganis (Media Karya Kesehatan, 2026)
The postpartum period is a critical phase that requires optimal care to prevent maternal and neonatal complications. However, postpartum mothers living in the wetland area of Sri Meranti Subdistrict, Pekanbaru City, still have limited knowledge and skills regarding postpartum care and proper breastfeeding techniques. This community service program aimed to analyze the effectiveness of community empowerment-based postpartum care education in improving the knowledge and breastfeeding skills of postpartum mothers in wetland areas. The program employed a pre-experimental design with a one-group pretest-posttest approach involving 30 postpartum mothers in the working area of the Umban Sari Public Health Center from July to September 2024. The intervention was conducted through health education, demonstrations, and re-demonstrations using booklets and educational videos. Evaluation was performed using a knowledge questionnaire and the LATCH Assessment Tool. Data were analyzed using a paired t-test with a 95% confidence interval. The results demonstrated a significant increase in postpartum mothers’ knowledge scores from 70.3 ± 8.5 to 89.7 ± 5.4 after the intervention (p=0.001). In addition, the total LATCH score increased from 5.4 ± 1.8 to 9.0 ± 0.9 after the intervention. All LATCH components showed improvement in breastfeeding technique ability  among postpartum mothers. Educational interventions grounded in community empowerment have the potential to enhance postpartum mothers’ knowledge and breastfeeding skills. Such interventions may be considered routine promotive strategies within maternal health services in wetland communities.Keywords: Community empowerment, health education, postpartum care, postpartum mothers, wetlands area.